2014
DOI: 10.1111/cbdd.12265
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Structure Optimization of a Series of Isatin Derivatives as Mycobacterium tuberculosis Chorismate Mutase Inhibitors

Abstract: In this study, the crystal structure of the Mycobacterium tuberculosis (MTB) enzyme chorismate mutase (CM) bound to transition state analogue (PDB: 2FP2) was used as a framework for virtual screening of the BITS-Pilani in-house database (2500 compounds) to identify new scaffold. We identified isatin as novel small molecule MTB CM inhibitors; further twenty-four isatin derivatives were synthesized and evaluated in vitro for their ability to inhibit MTB CM, and activity against M. tuberculosis as steps towards t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…All these modification resulted in very potent molecules as shown in Tables 2, 3 and 4. The N-benzyl amino (26)(27)(28)(29)(30), carboxamide (31)(32)(33)(34)(35) was well accommodated as the right hand core than their corresponding sulphonamide analogues (36- A structural insight into the interaction profile of the most potent compound inhibitor from the study compound 27 (Figure 4) showed the molecule to be involved in polar contact with Asn52, a crucial residue of gyrB. Additionally, a cation-π interaction was also observed between the amino group of Arg82 and thiazole of compound.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All these modification resulted in very potent molecules as shown in Tables 2, 3 and 4. The N-benzyl amino (26)(27)(28)(29)(30), carboxamide (31)(32)(33)(34)(35) was well accommodated as the right hand core than their corresponding sulphonamide analogues (36- A structural insight into the interaction profile of the most potent compound inhibitor from the study compound 27 (Figure 4) showed the molecule to be involved in polar contact with Asn52, a crucial residue of gyrB. Additionally, a cation-π interaction was also observed between the amino group of Arg82 and thiazole of compound.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar fashion, the thiourea (11-17 and 22-25) and the sulphonamide derivatives (36-40) were assembled from the 1-(5-nitrothiazol-2-yl)piperidin-4-amine scaffold (3) by reacting with their corresponding isothiocyante and sulphonyl chloride respectively. The amide derivatives (31)(32)(33)(34)(35) were developed by coupling the scaffold derivative (3) with the respective acid using propyl phosphonic anhydride as the coupling agent. Finally reductive amination of 1-(5-nitrothiazol-2-yl)piperidin-4-amine with desired aldehydes gave the designed amino derivatives (26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indoles, especially 1H-indole-2,3-dione (isatin) are the most prevalent heterocyclic scaffolds which have a broad spectra of medical applications such as anti-HIV, antiviral, anti-tumor, antifungal, antiangiogenic, anti-convulsant, and antiparkinsonian activity [6][7][8] . In particular, antituberculotic activity of various indole derivatives [9][10][11][12][13][14] and isatin derivatives [15][16][17][18][19][20][21][22] have attracted attention. The syn-thetic feasibility and extensive use of this scaffold have led to medicinal chemists to this ring which has also stemmed from the interest in the biological and pharmacological properties 23,24 .…”
Section: Introductionmentioning
confidence: 99%